Bim-based energy analysis and optimization using insight 360 (case study) - Ahmed M. Maglad; Moustafa Houda; Raid Alrowais; Abdul Mateen Khan; Mohammed Jameel; Sardar Kashif Ur Rehman; Hamza Khan; Muhammad Faisal Javed; Muhammad Faisal Rehman (Case Studies in Construction Materials, 2023)
Building information modeling (BIM) is a modern data information platform and management tool that promotes the development of green buildings. In Pakistan, the building sector consumes more than 50 % of total energy consumption and it is growing at annual rates of 4.7 % and 2.5 % in household and commercial sectors, respectively. The energy problem is the biggest single economic drag on Pakistan, the Pakistan BIM Council (PBC) is attempting to implement BIM adoption in the construction industry. Using Autodesk Insight 360 and Green Building Studio, an energy analysis and optimization case study of A-Block COMSATS Abbottabad, Pakistan is chosen. This study explores the energy performance of an academic building as a case study in order to optimize energy use by rotating the building 360 degrees at 45-degree intervals and utilizing BIM to install energy-efficient construction materials. Existing academic buildings have lower energy use and annual cost savings. The annual energy and financial savings are 585.10 kWh and 550 $, respectively. Applying factors to energy analysis can result in improved conceptual design with good environmental effectiveness, thus assisting in the pursuit of environmental sustainability.